An Analysis Of Factors Affecting The Financial Distress: The Case Of SOEs In Indonesia - Nikke Yusnita Mahardini; Bandi (Universitas Serang Raya, 2023)
The results of company performance can be determined by one of the internal factors of the company, namely the characteristics possessed by the CEO. Echelon theory explains that vision and strategy choices can be influenced by CEO experience and personality which ultimately affect company performance. The motivation for this study is that in Indonesia it is still rare to use a combination of CEO characteristics variables and financial indicators as factors that can affect financial distress in companies. The aim of this study is to examine the impact of CEO characteristics and financial indicators on financial distress in state-owned companies in Indonesia. This study uses state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange as the research population. The research data was tested using Logistic Regression Analysis. The research findings show that CEO age and sales growth have a significant effect on financial distress. While CEO tenure, CEO educational background, and total liabilities to total assets have no significant effect on financial distress.